2016
DOI: 10.1080/23723556.2016.1198299
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic degradation of focal adhesions underlies metastatic cancer dissemination

Abstract: Autophagy inhibition is being evaluated as a novel therapeutic strategy in multiple tumor types, but little is known about its implications for metastatic dissemination. We recently reported that autophagic degradation of paxillin through direct interaction with the autophagy protein LC3B is required for focal adhesion disassembly, Src-stimulated tumor cell motility, and metastasis. KEYWORDSAutophagy; cell motility; metastasis; paxillin; Src Despite decades of research, the treatment of metastatic disease rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Autophagy participates in FA turnover in this context, by degrading paxillin in auto phagosomes and disrupting FA. Sharifi et al found that inhibiting autophagy suppresses metastasis to the lungs and liver without affecting tumor cell proliferation in a metastatic 4T1 mouse model of breast cancer ( 8 , 133 ). Paxillin in breast cancer and melanoma metastasis serves as FA scaffolding and contains a LIR.…”
Section: The Interplay Of Autophagy and Metastasismentioning
confidence: 99%
“…Autophagy participates in FA turnover in this context, by degrading paxillin in auto phagosomes and disrupting FA. Sharifi et al found that inhibiting autophagy suppresses metastasis to the lungs and liver without affecting tumor cell proliferation in a metastatic 4T1 mouse model of breast cancer ( 8 , 133 ). Paxillin in breast cancer and melanoma metastasis serves as FA scaffolding and contains a LIR.…”
Section: The Interplay Of Autophagy and Metastasismentioning
confidence: 99%
“…This results in the encapsulation of cargo within an autophagosome, followed by their transport to the lysosome for degradation. It is thought that this selective process for the targeted turnover of focal adhesion components helps facilitate coordinated cell movement ( Kenific et al, 2016b ; Sharifi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of ECM–integrin engagement results in induced autophagy in several cellular models [ 62 , 63 ]. Furthermore, the basal level of autophagy regulates cell spreading by promoting cell protrusion extension [ 64 ] and is required for focal adhesion turnover and cell migration [ 65 ]. Interestingly, upon loss of ECM contact, the absence of nutrients does not per se induce autophagy, but rather a signaling mechanism that, “sensing” the cell environment, transduces the need for an alternative energy supply mechanism to the cell [ 66 ].…”
Section: Regulation Of Autophagymentioning
confidence: 99%